P70 'Code red': piloting a high-fidelity simulation workshop to address learning needs and raise awareness of resource management. (3rd November 2019) - Reid-McDermott, Bronwyn; Bhulbh, Áine de; Gilmore, Ruth; O'Gorman, Tom; Coohill, Margeret; Byrne, Dara
Abstract : Background: The primary cause of preventable trauma-related death is major haemorrhage. Activation of a Massive Transfusion Protocol (MTP) or 'Code Red' initiates the rapid and continuous supply of a large volume of blood products during life-threatening bleeds 1 . Activation of the protocol can be life-saving, however, 'Code Red' is a resource-intensive activity and significant risk is associated with inappropriate utilisation. An extended MTP can quickly deplete the supply of costly blood products and may lead to waste, thus contributing a significant cost burden to the healthcare system. Locally, the cost per unit of red cell concentrate is €295, plasma €116, platelets €650 and 1gm Fibrinogen €440. In 2018, there were 47 'Code Reds' in University Hospital Galway. A learning opportunity was identified to expand upon basic training in the management of MTPs and use High-Fidelity Simulation (HFS) to enhance staff awareness of deactivation, resource-utilisation and management of challenging MTP cases. Summary of work: A multidisciplinary team of midwives, nurses, porters, laboratory and blood bank staff and consultants in obstetrics, emergency medicine, anaesthesia and haematology engaged in addressing staff needs by developing a pilot HFS workshop. Three scenarios were developed targeting: Use of appropriate blood products for previously cross–matched blood Timely deactivation of a 'Code Red' and Management of a ward–based obstetric MTP (high–risk, low–frequency scenario) Feedback from participants and users was used to assess the feasibility and acceptability of the pilot session. Summary of results: The pilot session was run in March 2019 with 15 cross-discipline attendees. Feedback demonstrated that 100% of participants agreed or strongly agreed that the workshop addressed their learning needs, all agreed or strongly agreed that the workshop improved their ability to use skills related to the topic and all agreed or strongly agreed that the knowledge and skills they learned will be useful to them in their clinical job. Discussion, conclusions and recommendations: HFS offers a solution to both training clinical staff in improving the management of MTPs and in optimising the use of blood products so as to limit waste and resource depletion. References: Thomasson, R. R., Yazer, M. H., Gorham, J. D., Dunbar, N. M., & MTP Use Study Investigators, on behalf of the Biomedical Excellence for Safer Transfusion (BEST) Collaborative. (2019). International assessment of massive transfusion protocol contents and indications for activation. Transfusion.